ARTROSKOPSKA HIRURGIJA KOLJENA - Miroslav Kezunović; Žarko Dašić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Arthroscopic surgery is minimaly invasive endoscopic surgery. Knee joint is, because of its anatomy and fi siology when injured, best suited by the arthroscopic surgery. The objective of this work is to, using our material composed of 1257 patients treated by different surgical procedures in a period of 10 years, prove that this endoscopic method, as a revolutionary innovation in surgical treatment of knee in twentieth century, independent in diagnostics and surgical techniques.